2009
DOI: 10.1007/s00134-009-1536-y
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of non-invasive pressure support ventilation in infants with respiratory failure after extubation: a pilot study

Abstract: Objective: To evaluate the feasibility and effects of noninvasive pressure support ventilation (NIV) on the breathing pattern in infants developing respiratory failure after extubation. Design: Prospective pilot clinical study; each patient served as their own control. Setting: A nine-bed paediatric intensive care unit of a tertiary university hospital. Patients: Six patients (median age 5 months, range 0.5-7 months; median weight 4.2 kg, range 3.8-5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 11 publications
0
18
0
4
Order By: Relevance
“…The infants supported with PSV had lower respiratory rates (P Ͻ .001) and indices of WOB (P Ͻ .01) than did spontaneously breathing infants given no support. 35 The only randomized crossover study in neonates that has evaluated nasal PSV used the IV-200 SAVI ventilator (Sechrist Industries, Anaheim, California) and short binasal prongs. 36 Nasal PSV was delivered with the SAVI mode, which is different from conventional PSV.…”
Section: Noninvasive Ventilation Modes In Neonates Nasal Intermittentmentioning
confidence: 99%
“…The infants supported with PSV had lower respiratory rates (P Ͻ .001) and indices of WOB (P Ͻ .01) than did spontaneously breathing infants given no support. 35 The only randomized crossover study in neonates that has evaluated nasal PSV used the IV-200 SAVI ventilator (Sechrist Industries, Anaheim, California) and short binasal prongs. 36 Nasal PSV was delivered with the SAVI mode, which is different from conventional PSV.…”
Section: Noninvasive Ventilation Modes In Neonates Nasal Intermittentmentioning
confidence: 99%
“…2 In adult patients, high-level evidence supports the use of NIV in cardiogenic pulmonary edema, exacerbation of COPD, neuromuscular disorders, and respiratory distress in the immuno-compromised patient. 1 Although the application of NIV for pediatric patients is less established than for adult patients, NIV is considered acceptable in children with severe obstructive sleep apnea syndrome, 3 post-extubation respiratory failure, 4,5 immunocompromised acute respiratory failure, 6 and chronic respi-ratory failures such as neuromuscular disease 7 and cystic fibrosis. 8 While NIV theoretically allows for respiratory system muscle unloading, alveolar recruitment, oxygenation, and CO 2 wash-out, patient-ventilator asynchrony is a major issue leading to NIV treatment failure.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors report that NPPV compared with standard treatment after major abdominal surgery improved hypoxemia and reduced the need of intubation in adult population. NPPV application in children with postoperative respiratory failure was associated with improved respiratory effort, gas exchange, oxygen saturation and reduced need of intubation [2,[4][5][6]. It is also reported that exit of NPPV in atelectasis after extubation is near 100 % like in the second patient we referred.…”
Section: Introductionmentioning
confidence: 75%
“…This difference can be explained by defining anatomic compartments and their developmental differences in pediatric patients that influence susceptibility to ARF [1,2].…”
Section: Resultsmentioning
confidence: 99%